13 Exploring patient safety incidents arising from advance care planning for end of life patients: a mixed methods analysis of incident reports. Issue 3 (1st September 2018) - Dinnen, Toby; Williams, Huw; Noble, Simon; Edwards, Adrian; Kenkre, Joyce; Hibbert, Peter; Donaldson, Liam; Carson-Stevens, Andrew
Abstract : Introduction: Advance Care Planning (ACP) is an important component of patient centred end-of-life care (Houben et al. 2014; Brinkman-Stoppelenburg et al. 2014). However there is little evidence available on the safety of the process and its impact on quality of care. Aim: To characterise the nature of patient safety incidents arising around the ACP process for patients approaching end-of-life. Method: The National Reporting and Learning System (NRLS) collates patient safety incident reports across England and Wales. We performed a keyword search and manual review to identify relevant reports between 2005 and 2015. A mixed methods process combining structured data coding and exploratory descriptive analysis was undertaken to describe incidents underlying causes and outcomes. A thematic analysis identified areas on which to focus improvement initiatives. Results: We identified 67 incident reports in which patients experienced inadequate care due to issues with implementation of ACP. The most common source of error was (mis)communication of ACP (n=27) where documentation was lost or verbal handover was inaccurate. Over one third of reports (n=24) described an ACP not being followed. In the remaining reports (n=16) an ACP was not completed despite being appropriate. The most common contributory factor was inadequate staff knowledge (n=18). Common outcomes were cardiopulmonary resuscitation attempts contrary to a patient's wishes (n=18). Other outcomes included inappropriate treatment or transfer/admission. Conclusion: Our national level analysis identifies key priorities which should be explored in local contexts: specifically improving public and staff understanding and engagement with ACP and developing systems for recording and accessing ACP documentation across healthcare services. References: . Brinkman-Stoppelenburg A, Rietjens JA, Van Der Heide A. The effects of advance care planning on end-of-life care: A systematic review. Palliative Medicine2014;28:1000–25. . Houben CH, Spruit MA, Groenen MT, Wouters EF, Janssen DJ. Efficacy of advance care planning: A systematic review and meta-analysis. Journal of the American Medical Directors Association2014;15:477–89.